PEMBUATAN KOLEKTOR PELAT DATAR SEBAGAI PEMANAS AIR ENERGI SURYA DENGAN JUMLAH PENUTUP SATU LAPIS DAN DUA LAPIS - Dial Hayati; M. Ginting; W. Tambunan (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has conducted on "Fabrication of Flat Plate Collector as a Solar EnergyWater Heater with One and Two Covers”, using the experimental methods. Theexperiments were done by putting two types of solar collector on the area that the solarbeam can falls freely that perpendicularly to the surface of the collectors. Themeasurement were carried out on the intensity of solar radiation coming, hot watertemperature and the lost heat by using equipment of a simple pylheliometer and amercury thermometer. This measurements were done in 60 minutes interval every dayfor 14 days of observation. The results obtained for both types of flat plate collectorsproduced 66 liters of water every day. The two tier covered flat plate collector reachedthe highest temperature of 95 o C, which was higher than its of the single-tier coveredflat plate collector of 84 o C. This result was due to the more layers cover the less heatthat lost through the top surface of the flat plate collector. The highest temperature ofthe hot water that accommodated in the tank was 51 o C for the double layer collector lidand 47° C for the one layer of collector lid.